Electoral Violence and Political Alienation in Africa - God'stime Igiebor (African Journal of Political Science)
The research investigated the impact of electoral violence on voter alienation in Africa using Nigeria as a case. It attempted to ascertain the cause of low turnout of voters in the 2019 general elections and to determine the extent to which violence in elections can affect participation by gender, age and educational status. The aim of the study was to find out the relationship between violence and alienation in the Nigerian electoral process. The study adopted the survey research design and used data elicited from a sample of 1,200 respondents selected from six local government areas representing the six geo-political zones. The simple percentages and Chi- Square statistical techniques were utilized to test and determine the degree of association intrinsic in the stated hypotheses. The findings from the study show a positive relationship between violence and alienation. Thus, electoral violence is responsible for the alienation of voters from the electoral process. Consequently, the following suggestions are made: The federal and state governments should put on modalities to mitigate the incidences of violence during elections; perpetrators of electoral violence should be sanctioned; accordingly, while the African Union should closely monitor the various African States electoral processes to sanction any breach and mitigate incidences of violence in elections.